The Role of the Creative Economy in Improving Local Competitiveness: Case Study of Creative Cities in Indonesia - Amri, Amrin (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
The creative economy has become one of the main drivers of economic growth in various cities in Indonesia. This study aims to analyse the role of the creative economy sector in improving local competitiveness, focusing on creative cities in Indonesia. Through a systematic literature review (SLR) approach using the PRISMA method, this article evaluates research results from various academic sources and relevant reports. The study results show that creative cities can increase local competitiveness by encouraging innovation, cross-sector collaboration, and the creation of more sustainable job opportunities. The creative economy also strengthens local cultural identity, which is a selling point in the global market. However, challenges remain, including more digital infrastructure and adequate regulatory support. This article concludes that synergy between the government, the private sector, and the creative community is urgently needed to strengthen the creative economy ecosystem. The results of this study are expected to be the foundation for policymakers and creative industry players in designing more effective strategies to increase local competitiveness.